Risk-Based Leak Analysis of an LPG Storage Tank: A Case Study - Suroto Munahar; Bagiyo Condro Purnomo; Nanda Ferdiansyah; Eko Muh Widodo; Moehamad Aman; Retno Rusdjijati; Muji Setiyo (Universitas Pendidikan Indonesia, 2022)
Liquified petroleum gas (LPG) storage tanks are essential components for storing and distributing fuels. However, system failures due to inspection flaws increase the risk of leaks, fires, and explosions. Therefore, this study discussed the development of a safety system application applied to LPG storage tanks based on a risk-based leak (RBL) analysis. Data associated with risk factor values were obtained from an LPG storage tank in a gas distributor company. The risk of failure was calculated by analyzing the probability of failure (PoF) and the consequence of failure (CoF). The results showed that the level of risk observed was medium-high with a PoF in category 1 at a total damage factor value of 1. Furthermore, the CoF in category E was positioned with a consequence analysis value of 2381.29 m2 with an LPG storage tank life span of 33.5 years and an external inspection interval of five years.